Examining Prosociality in a Sample of Undergraduates in North-Central Nigeria: The Roles of Psychological Wellbeing, Emotional Intelligence and Perceived Self-Esteem - Bamikole Emmanuel, Agesin; AO, Olaseni (Happiness: Journal of Psychology and Islamic Science, 2025)
This study examined the roles of psychological wellbeing, emotional intelligence and perceived self-esteem on prosociality in a sample of undergraduates at the University of Ilorin, Kwara State, North-Central Nigeria. Adopting cross sectional survey design, 347 undergraduates from the University were conveniently sampled for this study. The age range of participants from 18 to 28 [M=19.8; SD=3.0] and they responded to standardized measures of Psychological Wellbeing Scale [α = .88], Emotional Intelligence [α = .85], Rosenberg Self-esteem Scale [α = .89] and Prosocial Behaviour Scale [α = .84]. Four hypotheses were formulated and tested. The result indicated that the independent variables; psychological wellbeing [β = .261, p > .05], emotional intelligence [β = .147, p > .05] and self-esteem [β = .255, p > .05] predicted prosocial behaviour. The joint contributions of all predictor variables were also significant [R2= .075, t = 5.096; p < .05]. Based on the findings of this study it was recommended that university management should lay emphasis on learning process to promote psychological wellbeing, emotional intelligence, self-esteem and prosocial behaviour among the students. Training programmes for effective development of the psychological wellbeing, self-esteem and emotional intelligence of the students should be designed to develop their emotional and social skills.